Evaluation of Duhat (Syzygium cumini) Leaves as Cytological Stain - Khassandra, Sabanal Atheena; Angela, Reyes Maria; Jay, Reyes Norvin; Renn, Soriano Ruff; Shanel, Tolentino; Bryan, Veneracion John; Ian, Ventenilla Ansel; Gabrielle, Vizconde Danica; Rose, Bremner Pamela (Asian Journal of Biological and Life Sciences)
Context: Staining is a vital histology process and synthetic stains, notably Hematoxylin and Eosin, are widely used in identifying tissues in the Histopathology section. Despite their remarkable efficiency in staining, these synthetic dyes pose a health hazard to laboratory workers, especially with frequent exposure. Hence, creating an alternative natural stain is imperative and has become of great interest in the research field. Objectives: This study aimed to develop a natural stain from the leaf extract of Syzigium cumini. Furthermore, to determine if the extract can be an alternative to Eosin as a stain for cytological specimens like urine and buccal samples, along with efficiency in staining, the study intends to determine the stain’s viability when stored over time at different storage conditions. Data sources: The ethics committee approved the research before starting and followed specific protocols for the participants’ data and safety. 180 slides were prepared from the participants’ buccal and urine specimens collected. The slides were then stained using the stain produced from the S. cumini extract and then viewed and graded under the microscope by four registered Medical Technologists. Results: The results demonstrated that distilled water and acetone, leaves extract, and acetone extract showed no significant difference compared to Eosin’s staining efficiency. On the other hand, distilled water leaf extract can also stain; however, it is inferior to Eosin.
Keywords: Alternative stain; Buccal; Chlorophyll; Duhat; Hematoxylin and eosin; S. cumini; Urine